The Effect of Weblog Utilization as A Learning Medium on Students’ Motivation in Biology - Anugra, Novia; Muhammad , Nurul Nisa (JURNAL BIOEDUKASI, 2025)
This study aims to determine the effect of using weblogs as a learning medium on students’ motivation to learn biology. The research employed a quasi-experimental approach with a pretest-posttest nonequivalent control group design. The subjects were 11th-grade science students at SMA Negeri 11 Makassar, consisting of an experimental group (35 students) and a control group (34 students). The instrument used was a learning motivation questionnaire based on the ARCS model (Attention, Relevance, Confidence, Satisfaction). The results of the descriptive statistical analysis showed that the students’ learning motivation in the experimental group increased more significantly than in the control group. The percentage of students who achieved high motivation scores in the control group was 85.29%, while in the experimental group it reached 100%. The inferential analysis using ANCOVA revealed a significance value of p = 0.02 (< 0.05), indicating a significant effect of weblog use on students’ learning motivation. The weblog effectively enhanced the aspects of attention, relevance, confidence, and satisfaction in learning. Therefore, weblogs can serve as an effective alternative digital learning medium to foster students’ motivation in the modern education era.